Dynamic generation of photonic spatial quantum states with an all-fiber platform - Alarcón, A.; Argillander, J.; Spegel-Lexne, D.; Xavier, G. B. (Optics express, 2023)
Photonic spatial quantum states are a subject of great interest for applications in quantum communication. One important challenge has been how to dynamically generate these states using only fiber-optical components. Here we propose and experimentally demonstrate an all-fiber system that can dynamically switch between any general transverse spatial qubit state based on linearly polarized modes. Our platform is based on a fast optical switch based on a Sagnac interferometer combined with a photonic lantern and few-mode optical fibers. We show switching times between spatial modes on the order of 5 ns and demonstrate the applicability of our scheme for quantum technologies by demonstrating a measurement-device-independent (MDI) quantum random number generator based on our platform. We run the generator continuously over 15 hours, acquiring over 13.46 Gbits of random numbers, of which we ensure that at least 60.52% are private, following the MDI protocol. Our results show the use of photonic lanterns to dynamically create spatial modes using only fiber components, which due to their robustness and integration capabilities, have important consequences for photonic classical and quantum information processing.